Inappropriate calibration and optimisation of pan-keratin (pan-CK) and low molecular weight keratin (LMWCK) immunohistochemistry tests: Canadian Immunohistochemistry Quality Control (CIQC) experience. Issue 3 (22nd January 2011) - Copete, Maria; Garratt, John; Gilks, Blake; Pilavdzic, Dragana; Berendt, Richard; Bigras, Gilbert; Mitchell, Sarah; Lining, Leslie Ann; Cheung, Carol; Torlakovic, Emina E
Abstract : Aims: Pan-cytokeratin (pan-CK) and low molecular weight cytokeratin (LMWCK) tests are the most common immunohistochemistry (IHC) tests used to support evidence of epithelial differentiation. Canadian Immunohistochemistry Quality Control (CIQC), a new provider of proficiency testing for Canadian clinical IHC laboratories, has evaluated the performance of Canadian IHC laboratories in two proficiency testing challenges for both pan-CK and LMWCK. Methods: CIQC has designed a 70-sample tissue microarray (TMA) for challenge 1 and a 30-sample TMA for challenge 2. There were 13 participants in challenge 1, and 62 in challenge 2. All results were evaluated and scored by CIQC assessors and compared with reference laboratory results. Results: Participating laboratories often produced false-negative results that ranged from 20% to 80%. False-positive results were also detected. About half of participating clinical laboratories have inappropriately calibrated IHC tests for pan-CK and LMWCK, which are the most commonly used markers for demonstration of epithelial differentiation. The great majority of laboratories were not aware of the problem with calibration of pan-CK and LMWCK tests because of inappropriate selection of external positive controls and samples for optimisation of these tests. Benign liver and kidney are the most important tissues to include as positive controls for both pan-CK and LMWCK. Conclusions: Participation in external quality assurance is important for peer comparison and proper calibration of IHC tests, which is also helpful for appropriate selection of positive control material and material for optimisation of the tests.